PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MINYAK SOLAR (PT WILLY DWI PERKASA) - Fakhira, Raisa; Gumilang Wirakada, Gugum (Jurnal Manajemen dan Pemasaran, 2024)
This study aims to determine the effect of service quality on purchasing decisions for diesel oil at PT Willy Dwi Perkasa. Service quality is measured using five dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. While purchasing decisions are measured by five indicators, namely problem recognition, information search, alternative evaluation, purchasing decisions, and post-purchase behavior With a descriptive quantitative approach method Data analysis techniques using simple linear regression with 30 respondents. The results of this study indicate that there is an influence of Service Quality on purchasing decisions of 81.9%